AVALIAÇÃO DE DIFERENTES MÉTODOS ANALÍTICOS E EFEITOS DA ORIGEM GEOGRÁFICA, VARIETAL E CULTIVO AGRONÔMICO NA COMPOSIÇÃO QUÍMICA E ATIVIDADE ANTIOXIDANTE DE SUCOS DE UVA PONTA GROSSA 2015 - Margraf, Tiago (2015)
Worldwide, the consumption of purple grape juice has grown since several studies point to the potential health benefits, combined with a balanced diet and regular physical exercise. These potential benefits are related to the bioactive compounds present in this fruit and other plants, responsible for the inhibition of reactive oxygen and nitrogen species, formed in oxidative and inflammatory processes in the human body. In this context, researchers have tried and tested fast, inexpensive, accurate and reproducible methods, which are able estimating the content of bioactive compounds in beverages and foods. In this scenario, the objectives of this study were divided in two experimental chapters, where the Chapter II had as purpose to test and validate a more selective spectrophotometric method than the Folin-Ciocalteu assay, to quantify the content of phenolic compounds in grape juice. Already the Chapter III had as purpose to characterize n = 62 juices Brazilian purple grapes from different geographic origins (RS, PR and SC), agronomic (organic and conventional) and genotypic (Bordo, Isabel and Concord) about its physicochemical and chemical properties, and in vitro antioxidant activity using chemical and biological systems. The results showed that the Prussian Blue method has low detection (0.27 mg L-1) and quantification limit (0.92 mg L-1), and a high association (r = 0.923, p < 0.0001) with the standard method of Folin-Ciocalteu reagent for the grape juice matrix, and also a faster reaction and high selectivity compared to the Folin-Ciocalteu assay. Furthermore, the geographical origin and the grape variety proved to be the most important factors in distinguishing juices (p < 0.05) for antioxidant activity and some chemical markers. However for the organic and conventional juices, except for some phenolic acids determined by high-performance liquid chromatography, there were no statistically significant distinctions (p > 0.05). A total of n = 18 grape juices were characterized by presenting high, intermediate and low antioxidant activity in vitro using four different methodologies (Scavenging of ABTS●+ radical; Ferric-reducing antioxidant power - FRAP; Total reducing power; and Reducing potential of the hydrophilic phenolic compounds - RPHPC) and were subjected to analysis of the inhibition of lipid peroxidation at 37 °C by means of a biological assay in buffered medium at pH 7.4. The inhibition of lipid peroxidation of the grape juice showed a significant correlation (r ≥ 0.505; p ≤ 0.02) with other antioxidant activity assays, concluding that the antioxidant activity in vitro of Brazilian purple grape juice has association either by chemical methods or by biological means.